Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675177
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Developers' Coordination in the IDE

Abstract: Teamwork in software engineering is time-consuming and problematic. In this paper, we explore how to better support developers' collaboration in teamwork, focusing on the software implementation phase happening in the integrated development environment (IDE). Conducting a qualitative investigation, we learn that developers' teamwork needs mostly regard coordination, rather than concurrent work on the same (sub)task, and that developers successfully deal with scenarios considered problematic in literature, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 64 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…• Review -Reviewers have to understand the code changes of all the activities at once [6]- [8]; • Reversion -Developers have to revert all changes of a problematic commit even when only the code change of one activity is problematic [1]; • Integration -Integrators have to merge or reject whole commits, e.g., they will typically reject a code formatting operation and a bug fix included in the same commit [9]; • Historical analysis -Researchers need to associate activities to files to conduct statistical analyses while, e.g., mining software repositories [4].…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Review -Reviewers have to understand the code changes of all the activities at once [6]- [8]; • Reversion -Developers have to revert all changes of a problematic commit even when only the code change of one activity is problematic [1]; • Integration -Integrators have to merge or reject whole commits, e.g., they will typically reject a code formatting operation and a bug fix included in the same commit [9]; • Historical analysis -Researchers need to associate activities to files to conduct statistical analyses while, e.g., mining software repositories [4].…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Version Control Systems (VCS), such as Git and Subversion, allow programmers to control changes to source code and make it possible to find who made each software change, when, and where. This information is important to support both the coordination of developers working in teams [1] and the creation of many recommendation and prediction systems related to software quality [2].…”
Section: Introductionmentioning
confidence: 99%
“…We grouped the remaining articles (23 articles, 50%) into studies that focus on the programming environments used by professional programmers. The articles show the following types of improvements for programming environments: (i) related to error comprehension [48]- [51]; (ii) in the visualization of codes [52]- [55]; (iii) in the ease of code refactoring [56], [57]; and (iv) the ease of making code changes and maintaining control over changes [58]- [61].…”
Section: B: Programmer Environment For Programmersmentioning
confidence: 99%
“…In addition to loss of time and money, this causes frustration [9,42]. Studies have shown that these problems can be avoided by following strategies such as effective communication within the team [28], and developing awareness about others' changes that have a potential to incur conflicts [22].…”
Section: Introductionmentioning
confidence: 99%